2001
DOI: 10.1021/jo001504i
|View full text |Cite
|
Sign up to set email alerts
|

α-Thiocyanation of Carbonyl and β-Dicarbonyl Compounds Using (Dichloroiodo)benzene−Lead(II) Thiocyanate

Abstract: The combination reagent (dichloroiodo)benzene and lead(II) thiocyanate in dichloromethane effects oxidation of various enol silyl ethers, ketene silyl acetals, and beta-dicarbonyl compounds, thereby providing an efficient and convenient method for alpha-thiocyanation of carbonyl and beta-dicarbonyl compounds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(20 citation statements)
references
References 29 publications
0
20
0
Order By: Relevance
“…This is in contrast with the optimum conditions to synthesise these compounds since the isomerisation thiocyanate-isothiocyanate can occur in solution at temperatures above 50ºC and/or acidic conditions. 10,16,22 For these reasons, the development of new procedures for the easy and rapid synthesis of thiocyanate derivatives in high yields is required. Herein we report our efforts in the preparation of versatile thiocyanate compounds in aqueous mixtures at high substrate concentrations and further conversion into the interesting heterocyclic 2-imino-1,3-oxathiolane system employing mild reaction conditions and cheap reagents.…”
mentioning
confidence: 99%
“…This is in contrast with the optimum conditions to synthesise these compounds since the isomerisation thiocyanate-isothiocyanate can occur in solution at temperatures above 50ºC and/or acidic conditions. 10,16,22 For these reasons, the development of new procedures for the easy and rapid synthesis of thiocyanate derivatives in high yields is required. Herein we report our efforts in the preparation of versatile thiocyanate compounds in aqueous mixtures at high substrate concentrations and further conversion into the interesting heterocyclic 2-imino-1,3-oxathiolane system employing mild reaction conditions and cheap reagents.…”
mentioning
confidence: 99%
“…[173] Prakash and Moriarty reported that the combination of (dichloroiodo)benzene and lead(II) thiocyanate effects thiocyanation of β-ketoesters and 1,3-diketones (Scheme 91). [174] [Bis(thiocyanato)iodo]benzene is believed to be the active reagent in this process. Ketones and esters are not reactive under these conditions, but the α-thiocyanated products can be obtained from the corresponding silyl enol ethers.…”
Section: Scheme 90 Azidation Of Ketonesmentioning
confidence: 99%
“…Ketones and esters are not reactive under these conditions, but the α-thiocyanated products can be obtained from the corresponding silyl enol ethers. [174] An improved method for thiocyanation of 2-arylindan-1,3-diones was later found, where (dichloroiodo)benzene was combined with potassium thiocyanate. [175] Scheme 91 Thiocyanation of dicarbonyl compounds.…”
Section: Scheme 90 Azidation Of Ketonesmentioning
confidence: 99%
“…As part of our ongoing program directed toward the unique applications of organohypervalent iodine reagents in organic synthesis, we have shown that organoiodine(III) reagents such as iodobenzene diacetate (IBD) [2] and [hydroxy(tosyloxy)iodo]benzene (HTIB, Koser's reagent) [3] are excellent reagents for the oxidation of phenolic compounds [4], ␣-functionalization of carbonyl compounds [5], and synthesis of a wide variety of heterocyclic compounds [6], including biologically active compounds [7]. In continuation of these encouraging reports, we have developed an efficient and easy method for the synthesis of new 3,9-diaryl-bis-1,2,4-triazolo [4,3-a] [4,3-c]pyrimidines 4 as potential antibacterial agents.…”
Section: Introductionmentioning
confidence: 99%